Pengaruh Aktiva Pajak Tangguhan, Beban Pajak Tangguhan dan Corporate Social Responsibility Terhadap Agresivitas Pajak - Reti Agustina; Aris Sanulika (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to test and obtain empirical evidence regarding the influence of deferred tax assets, deferred tax expenses and corporate social responsibility on tax aggressiveness. Linear research is a theoretical application that is generally obtained from lectures, in addition to coursework, lineal research also adds insight and knowledge about the influence of the activity of deferred taxes, deferred tax burdens, and Corporate Social ResponsibilityonTaxAggressiveness.This research uses a sample of Energy sector companies listed on the Indonesia Stock Exchange (BEI) in 2018-2023 with a population of 87 companies. The method for determining the research sample used a purposive sampling method, obtaining 14 company samples with an observation period of 6 years, obtaining 84 research data. The type of research in this research is quantitative research. The analysis technique used is panel data regression which is processed using Eviews version 12 software. The results of this research show that partially (1) Deferred Tax Assets do not have a significant effect on Tax Aggressiveness (2) Deferred Tax Expenses have a significant effect on Tax Aggressiveness and (3) Corporate Social Responsibility has no significant effect on Tax Aggressiveness. Simultaneously, deferred tax assets, deferred tax expenses and corporate social responsibility influence tax aggressiveness.